Chronic subdural haematoma in antithrombotic cohorts: characteristics, surgical outcomes, and recurrence. (3rd July 2020) - Zhang, Peng; Li, Yuping; Huang, Jiannan; Zhang, Hengzhu; Wang, Xiaodong; Dong, Lun; Yan, Zhengcun; She, Lei
Abstract: Objective: With the continuing increase of the aged population, neurosurgeons face increasing numbers of chronic subdural haematoma (CSDH) patients using antithrombotic (AT) drugs, i.e., anticoagulants (ACs) and antiplatelets (APs). However, there are few case reports that address this cohort and their outcomes. Here, a retrospective analysis of CSDH patients on AT therapies was performed to investigate their clinical characteristics, surgical outcomes, and postoperative recurrence. Methods: We analysed 546 CSDH patients who underwent surgery at the Subei People's Hospital of Jiangsu province from January 2014 to December 2017. The patients were divided into groups based on their history of preceding AT treatments as well as recurrence. The clinical data, surgical outcomes, and recurrence were collected for further analysis. Results: A total of 124 patients (22.7%) were receiving AT therapy, including 43 patients (7.9%) taking ACs and 81 patients (14.8%) taking APs. AT cohorts exhibited significantly higher non-traumatic CSDH, more serious pre-illness status, and larger haematoma volume, compared with the control patients. The haematoma clearance rate, duration of YL-1 needle, complications, and functional outcomes did not differ after novel YL-1 needle drainage, whereas a higher recurrence, mortality, and prolonged length of stay were observed in the AT group. Multivariate regression of postoperative recurrence within 3 months revealed that preoperative consciousness disorders, AC therapy, haematoma volume, and operative complications were significant predictive factors of CSDH recurrence. However, AP therapy was not associated with recurrence. Conclusions: The use of ATs causes large haematoma volumes that aggravate the severity in CSDH patients and is more prevalent among non-traumatic patients. AC therapy was a risk factor for CSDH recurrence, whereas AP therapy was not.